Review of mechanical vapour compression refrigeration system part 2: performance challenge - Mahmood, R. A.; Ali, O. M.; Al-Janabi, A.; Al-Doori, G.; M. M., Noor (Sciendo, 2021)
Reducing energy consumption and providing high performance for a vapour compression refrigeration system are big challenges that need more attention and investigation. This paper provides an extensive review of experimental and theoretical studies to present the vapour compression refrigeration system and its modifications that can be used to improve system's performance and reduce its energy consumption. This paper also presents the challenges that can be considered as a gab of research for the future works and investigations. Cooling capacity, refrigerant effect, energy consumption can be improved by using vapour injection technique, natural working fluid, and heat exchanger. Based on the outcome of this paper, vapour injection technique using natural refrigerant such as water can provide ultimate friendly refrigeration system. Future vision for the vapour compression refrigeration system and its new design technique using Computational Fluid Dynamic (CFD) is also considered and presented.